A relationship between Single Nucleotide Polymorphism (SNP) in HSD11β1 and ADIPOQ genes and obesity related features in children and adolescents submitted on physical exercises - Cardozo Gasparin, Caroline; Leite, Neiva; Lehtonen Rodrigues de Souza, Ricardo; Viater Tureck , Luciane; E. Milano-Gai , Gerusa; Pizzi, Juliana; R. Silva, Larissa; de Fátima Aguiar Lopes , Maria; A. Lopes, Wendell; Furtado-Alle, Lupe (Brazilian Journal of Implantology and Health Sciences, 2024)
Obesity have overloaded the public health system and it is considered a multifactorial trait. This study aimed to verify if Single Nucleotide Polymorphisms (SNP) in ADIPOQ (rs1501299) and HSD11β1 (rs12086634) genes influence the anthropometric and biochemical outcomes (Body Mass Index (BMI), Abdominal Circumference (AC), Low Density Lipoprotein (LDL-C), High Density Lipoprotein (HDL-C), Triglycerides (TG), Total Cholesterol (TC) and Glucose (Glu)) before and after practicing physical exercises training modalities, in a sample of 126 Southern Brazilian children and adolescents. Genotyping were performed by Taqman allelic discrimination. T carriers of rs1501299 had a higher BMI reduction (b*=0.28±0.12; p=1.70.10-2) and TT genotype of rs12086634 influence on AC reduction (b*=-0.33±0.13; p=1.24.10-2), independent of sex, age and modality of physical exercise. Ultimately, we observed an association of SNP of ADIPOQ and HSD11β1 gene with anthropometric variables early in life and the importance of physical exercise on biochemical and obesity related features.